(untitled) (Res Medica, 2014)
This is a short collection of interesting items pertinent to medicine and science in general. It gives a taste of some of the current work in hand around the world. We would welcome any contributions of this nature, just a short chatty narrative of an interesting or amusing article that you have seen or read. Coffee A recent study1 of ‘healthy’ moderate drinkers (consuming 4-6 cups per day; moderate? I call that low.) showed that on switching to decaffeinated (in a blind trial) many developed headaches for 2-3 days. One good reason not to stop? Need another good reason? Here goes ... A report(2) from Sheffield states that coffee induces a desire to defaecate (by increasing activity in the rectosigmoid) in nearly 30% of people. For some unexplained reason this predominately affects women! - a cheap cure for constipation? Unfortunately the effects of the evil brew doesn’t end there; about the same number of people (30% of the population) find that coffee aggravates their symptoms of irritable bowel syndrome. Will the coffee saga never end?